Impact time control based on time-to-go prediction for sea-skimming antiship missiles - Tahk, Min-Jea; Shim, Sang-Wook; Hong, Seong-Min; Choi, Han-Lim; Lee, Chang-Hun (IEEE, 2018)
This paper proposes a novel approach for guidance law design to satisfy the impact-time constraints for a certain class of homing missiles. The proposed guidance law provides proper lateral acceleration commands that make the impact time error converge to zero by the time of impact. This scheme can be applied to any existing guidance law for which a formula of predicted time to go is available. Convergence of time-to-go errors is supported by Lyapunov stability. The optimal guidance law and the impact angle control guidance law are extended by the proposed method for impact-time-control guidance and impact-time-and-angle-control guidance, respectively. The performance of the extended guidance laws is demonstrated by numerical simulation.